From genes to fields: Marker-assisted selection for nematode resistance in crops - Dababat, Abdelfattah A.S.; Paulitz, Timothy; Salah-Eddine Laasli; Lahlali, Rachid; Li, Honglian; Mokrini, Fouad; Dreisigacker, Susanne (Roots Press, 2025)
Plant-parasitic nematodes (PPNs) are one of the serious threats to agricultural production worldwide, causing enormous economic losses and posing a threat to food security. This review outlines a few important groups of PPNs, their economic losses, and current control approaches. Marker Assisted Selection (MAS) has been recognized as a precise and efficient approach for developing nematode-resistant cultivars and an environmentally friendly alternative to conventional control practices. Genome-Wide Association Studies (GWAS) thereby provide a way of identifying novel resistance loci and deciphering the genetic basis of resistance traits. MAS guided by validated GWAS results have therefore immense prospects for enhancing resistance breeding, reducing over-dependence on nematicides, and fostering healthy agricultural systems. Future efforts should focus on integrating molecular with field-based approaches to maximize benefits in the control of nematodes.